Gestational diabetes mellitus, pre-gestational BMI and offspring BMI z-score during infancy and childhood: 2004 Pelotas Birth Cohort - Aluísio J D Barros; Iná S Santos; Alicia Matijasevich; Christian Loret de Mola (BMJ Open)
Objective Gestational diabetes mellitus (GDM) affects a significant number of women. Evidence regarding the association between GDM and offspring body mass index (BMI) is unclear due to small samples and lack of adequate confounding control. The objective of this study was to investigate the association between GDM and offspring BMI z-scores from birth to early adolescence and to examine the role of maternal pre-gestational BMI in this relationship.Design Prospective study.Setting Pelotas 2004 Birth Cohort, Brazil.Participants Cohort participants that were followed-up from birth up to early adolescence (~3500) and their mothers.Primary outcome measures BMI z-scores at birth, 3, 12, 24, 48 months and 6 and 11 years of age, calculated according to the WHO growth charts.Results Unadjusted and adjusted linear regressions were performed and interaction terms between maternal pre-gestational BMI and GDM were included. Prevalence of self-reported GDM was 2.6% (95% CI 2.1% to 3.1%). The offspring BMI z-scores (SD) at birth, 3, 12, 24, 48 months and at 6 and 11 years were 0.10 (1.12), –0.47 (1.10), 0.59 (1.10), 0.59 (1.08), 0.78 (1.32), 0.70 (1.43) and 0.75 (1.41), respectively. Unadjusted regression models showed positive associations between GDM and offspring BMI z-scores at birth, 6 and 11 years. After adjustment, the associations attenuated towards the null. Statistical evidence of effect modification between maternal pre-gestational BMI and GDM was observed at birth (p=0.007), with the association between GDM and offspring BMI z-score being apparent only in those children born to overweight or obese mothers (β=0.72, 95% CI 0.30 to 1.14 and β=0.61, 95% CI 0.20 to 1.01, respectively).Conclusions We observed that in the association between GDM and offspring BMI z-scores, there is a predominant role for maternal nutritional status before pregnancy and that the association between GDM and newborn’s BMI is apparent only among those born to overweight or obese mothers.